2019
DOI: 10.1111/sji.12811
|View full text |Cite
|
Sign up to set email alerts
|

Impaired polysaccharide responsiveness without agammaglobulinaemia in three patients with hypomorphic mutations in Bruton Tyrosine Kinase—No detection by newborn screening for primary immunodeficiencies

Abstract: Hypomorphic mutations in the gene encoding Bruton tyrosine kinase (BTK) may result in milder phenotypes and delayed diagnosis of B-cell related immunodeficiencies due to residual BTK function. Newborn screening for kappa-deletingrecombination-excision circles (KRECs) reliably identifies classical X-linked agammaglobulinaemia (XLA) patients with profound B-cell lymphopenia at birth but has not been evaluated in patients with residual BTK function. We aimed to evaluate clinical findings, BTK function and KREC co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Additional functional evaluations revealed mild defects in B cell activation but not in protein expression, suggesting residual function of BTK. Similar to our findings, patients with a late-onset of BTK insufficiency and less severe phenotype due to hypomorphic mutations in this gene have also been reported (88,91). This case demonstrates the importance of also considering hypomorphic mutations in adult patients besides complete loss-of-function (amorphic) mutations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additional functional evaluations revealed mild defects in B cell activation but not in protein expression, suggesting residual function of BTK. Similar to our findings, patients with a late-onset of BTK insufficiency and less severe phenotype due to hypomorphic mutations in this gene have also been reported (88,91). This case demonstrates the importance of also considering hypomorphic mutations in adult patients besides complete loss-of-function (amorphic) mutations.…”
Section: Discussionsupporting
confidence: 90%
“…Hypomorphic mutations in other IEI genes (BTK, GATA2, IL2RG, JAK3, RAG1, RAG2, etc.) have been previously found in patients with antibody deficiency and milder phenotypes or in CVID patients (85)(86)(87)(88)(89)(90). Interestingly, P215, who presented with hypogammaglobulinemia, low circulating B cells, and impaired vaccine responses, carried a new hypomorphic variant in the kinase domain of BTK.…”
Section: Discussionmentioning
confidence: 89%
“…Btk plays a key role in B-cell development and maturation, participating in the intracellular pre-BCR and BCR-induced Ca 2+ influx, being the latest critical step for several proliferative responses at the Pre-B-I and several other peripheral stages. The R562Q variant decreases Ca 2+ influx on anti-IgM stimulation in the patient’s B cells, suggesting an enzymatic impairment of the mutated tyrosine kinase domain, as previously reported in other hypomorphic mutations ( 25 ) with Btk-deficient B-cells that exhibit defective anti-IgM calcium mobilization but normal induction of PLCγ2 tyrosine phosphorylation ( 37 ). Similar findings in point mutations from kinase, SH and PH domains in DT40 cells have shown that Btk deficiency causes a reduction in hydrogen peroxide levels induced by the calcium response, and this altered calcium signaling causes the suppression of IP3 production and phospholipase PLCγ2 ( 38 ).…”
Section: Discussionsupporting
confidence: 72%
“…Classical male XLA patients present severe agammaglobulinemia due to the severe reduction or absence of peripheral B cells, and experience frequent infections ( 7 ). However, BTK variants associated with atypical XLA case presentations have been reported, in patients with normal: IgG levels ( 21 ), selective IgM deficiency ( 22 ) with a leaky phenotype (in a Japanese family) ( 23 ), a diagnosis in adulthood but with a history of recurrent infections ( 24 ) and with impaired polysaccharide responsiveness without marked hypogammaglobulinemia ( 25 ). Although the gene variant present in our patient (R562Q) had not been previously described, other variants have been reported in the same residue as being probably pathogenic (R562W, R562L, R562P) ( 26 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, BTK is necessary for generating a pool of mature B cells capable of responding to foreign Ag to provide Ab-mediated host defense against infection pathogens. Interestingly, a number of cases have been reported of males who presented with recurrent bacterial infections, hypogammaglobulinemia or Ig subclass deficiencies and variable numbers of circulating B cells, and were found to have hypomorphic variants in BTK that had modest effects on B cell development and differentiation ( Geier et al, 2018 ; Krüger et al, 2020 ; Mitsuiki et al, 2015 ; Toker et al, 2022 ). This highlights the importance of validating variants in genes that are known to cause disease and identified in individuals with atypical presentations of classic IEIs.…”
Section: Introductionmentioning
confidence: 99%